2019
DOI: 10.3390/su11020431
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Affective Antecedents of Consumers’ Satisfaction: A Systematic Review of Two Research Approaches

Abstract: The study of consumers’ satisfaction has generated empirical research in the last few decades, with new challenges, such as a specific lens on online consumers’ satisfaction. During the last decades, two well-differentiated research traditions can be observed: cognitive and affective. A wide range of antecedents of consumers’ satisfaction has been proposed. The present contribution empirical research conducted under these two perspectives to determine which variables are related to satisfaction, the direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 64 publications
1
18
0
3
Order By: Relevance
“…If consumers believe that a brand reflects their identity, they combine the features of the brand with self-awareness and selfdefinition (Gordon and Luo, 2011). Therefore, when consumers identify with a brand, they connect with it, allowing for an enjoyable shopping experience and playing a crucial role in the selection of the product (Palací et al, 2019). This intrinsic connection with the brand encourages consumers to participate in a higher level of information sharing (i.e., word-of-mouth marketing), thus achieving the brand's interests (Shin et al, 2018).…”
Section: Social Value Of Luxury Brandsmentioning
confidence: 99%
“…If consumers believe that a brand reflects their identity, they combine the features of the brand with self-awareness and selfdefinition (Gordon and Luo, 2011). Therefore, when consumers identify with a brand, they connect with it, allowing for an enjoyable shopping experience and playing a crucial role in the selection of the product (Palací et al, 2019). This intrinsic connection with the brand encourages consumers to participate in a higher level of information sharing (i.e., word-of-mouth marketing), thus achieving the brand's interests (Shin et al, 2018).…”
Section: Social Value Of Luxury Brandsmentioning
confidence: 99%
“…The authors noted further that employees with positive affectivity has positive outlook of themselves and the environment they found themselves. Palaci, Salcedo, and Topa (2019) found that affective predictors have strong impact when services are hired and consuming goods. This suggests that there is a relationship between service delivery and affectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Cooper, 1993). Dalam beberapa penelitian yang dilakukan disebutkan bahwa kriteria yang sering digunakan untuk menentukan kota tujuan MICE antara lain adalah aspek aksesibilitas, dukungan para pemangku kepentingan terkait, potensi daya tarik wisata, ketersediaan akomodasi, adanya infrastruktur MICE (tempat pertemuan, tempat pameran), imej dari destinasi, lingkungan secara umum, dan sumber daya manusia (Alain Decrop & Cozak, 2014;Boo & Kim, 2019;F Palaci, 2019).…”
Section: Pendahuluanunclassified
“…Sejumlah kriteria itulah yang kemudian menjadi pertimbangan-pertimbangan para delegasi ketika hendak berpartisipasi pada suatu event. Tidak hanya yang berkaitan dengan aspek fisik tetapi keputusan berpartisipasi juga dipengaruhi oleh aspek non fisik yaitu motivasi yang terkait erat dengan nilai kepuasan yang berhubungan dengan aspek psikis (F Palaci, 2019;Goldblatt, 2005). Aspek psikis dalam ini misalnya persepsi tentang destinasi, citra, daya tarik, kualitas pelayanan, dan atribut lainnya yang disukai (Chaberek & Ziółkowska, 2017).…”
Section: Pendahuluanunclassified